Law 1697 of 2013 Stamp Pro National University of Colombia and other state universities of Colombia. From legal subjectivity to practical application (2019)
The stamp Pro National University of Colombia and other State Universities of Colombia is a parafiscal contribution created by the Congress of the Republic through Law 1697 of 2013, in order to strengthen state universities at the national level. For the distribution of resources it was established that during the first five years of entry into force 70% of the collected will be allocated to the National University of Colombia and the remaining 30% will be distributed in the other state universities nationwide. These resources should be allocated to topics of locative improvement of the universities, modernization, subsidies to students, development of new university campuses. After five years of entry into force, a redistribution of resources will be made, leaving 30% of the proceeds for the National University of Colombia and the remaining 70% will be distributed in the other state universities. The generating fact of this stamp is constituted by public works contracts and related to such as studies, designs, project management, auditing, supervision, among others, signed by national entities and whose execution is with the General Budget of the Nation.